Contemporary Pedagogies in Teacher Education and Development - Weinberger, Yehudith; Libman, Zipora (IntechOpen, 2018)
As with most dynamic activities that are based on social and cultural contexts and rely on interactions, education is a complex and often ambiguous endeavor. Despite this complexity, scholars and educators are often required to find ways of defining and explaining what "good" teaching is and to incorporate these conclusions into teacher education. This book contains eight scholarly articles from various countries around the world and offers unique and up-to-date perspectives on relevant practices and pedagogies for teachers' professional education and development. In this international book, it is argued that there is a significant inspiration and enrichment to be gained by investigating the policies and practices of teacher education systems from all over the world.